192 Effects of dam relative calving date on progeny performance. (5th December 2019) - Mercadante, Vitor R G; White, Robin R; Currin, John; Bradford, Heather L; Clarke, Sherrie; Stewart, Jamie F; Dias, Nicholas W; Timlin, Claire; Pancini, Stefania
Abstract: The objective of this study was to establish the relationships between when a cow was born within the calving season and the performance of her offspring. Data from the Virginia Department of Corrections beef cattle herds were collated for 7 locations over 7 years (2010 to 2017), with 2 calving seasons per year. Data from Spring of 2011 were missing. The full dataset contained 19, 253 individual animal observations. Within each location, year, and calving season combination, the calving season was defined as starting when the first calf was born and terminating when the final calf was born. The relative calving date (RCD) within each calving season was defined by calculating the number of days between when the calving occurred and when the calving season started, divided by the length of the season in days. For heifer calves that were retained as replacement heifers (n = 2, 800), the RCD and birth weight of their calves were used as response variables of a mixed-effect model with fixed effects of dam RCD, season (fall vs spring), and calf sex. All 2 and 3 way interactions were also included as fixed effects. Both calving year and sire were used as random effects. Fixed effects were iteratively removed from the model when non-significant; however, non-significant linear terms were retained if involved in a significant interaction term. The final calf RCD model included significant effects of dam RCD (P = 0.006), season (P < 0.001), calf sex (P = 0.0737), and the interaction between dam RCD and calf sex (P = 0.055). The final calf birth weight model included only linear terms for calf sex (P < 0.001) and dam RCD (P = 0.029). Least square means for these relationships are depicted in Table 1.